Watching women's liberation, 1970 : feminism's pivotal year on the network news - Dow, Bonnie J. (University of Illinois Press, 2014)
In 1970, ABC, CBS, and NBC - the 'Big Three' of the pre-cable television era - discovered the feminist movement. From the famed sit-in at Ladies' Home Journal to multi-part feature stories on the movement's ideas and leaders, nightly news broadcasts covered feminism more than in any year before or since, bringing women's liberation into American homes. In this book, Bonnie J. Dow uses case studies of key media events to delve into the ways national TV news mediated the emergence of feminism's second wave.